2021
DOI: 10.1002/agj2.20465
|View full text |Cite
|
Sign up to set email alerts
|

Harvest management and genotype effects on sunn hemp forage characteristics

Abstract: Sunn hemp (Crotalaria juncea L.) is an annual legume widely used as cover crop; however, there is potential to use it as forage. The objective of this study was to evaluate forage characteristics of 5 sunn hemp genotypes (HA, nutritive value, N fixation and nematode control), and beef heifer responses (intake and digestibility) to sunn hemp dietary inclusion. Two experiments were conducted at Ona, FL in 2016 and 2017. In Exp. 1, treatments were the factorial arrangement of five sunn hemp genotypes (AU Golden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…Biomass accumulation ranged for 0.2-5.1 Mg ha −1 in the rainfed study and 1.2-4.2 Mg ha −1 in the irrigated study, which is comparable to reported yields for sunn hemp. Schomberg et al (2007) found that at 60 DAP sunn hemp biomass yielded 4.6 and 5.0 Mg ha −1 at their locations in Tiffton, GA, and Watkinsville, GA. Cherr et al (2006) reported sunn hemp yields of 4.0 Mg ha −1 at 60 DAP in Citra, FL, and Garzon et al (2020) found biomass yield from 1.0 to 3.3 Mg ha −1 at 60 DAP in Ona, FL. Our biomass accumulation falls within the reported ranges for southern growing locations where the crop is typically grown.…”
Section: Biomass Accumulationmentioning
confidence: 98%
“…Biomass accumulation ranged for 0.2-5.1 Mg ha −1 in the rainfed study and 1.2-4.2 Mg ha −1 in the irrigated study, which is comparable to reported yields for sunn hemp. Schomberg et al (2007) found that at 60 DAP sunn hemp biomass yielded 4.6 and 5.0 Mg ha −1 at their locations in Tiffton, GA, and Watkinsville, GA. Cherr et al (2006) reported sunn hemp yields of 4.0 Mg ha −1 at 60 DAP in Citra, FL, and Garzon et al (2020) found biomass yield from 1.0 to 3.3 Mg ha −1 at 60 DAP in Ona, FL. Our biomass accumulation falls within the reported ranges for southern growing locations where the crop is typically grown.…”
Section: Biomass Accumulationmentioning
confidence: 98%
“…The data suggested that it has a moderate level of soluble TPN fraction (179 g/kg total N), which was approximately equal to that of a haft of oats (430 g/kg total N) [26]. The nutritive value of an SH crop can vary among genotypes and as a result of other factors such as soil, fertilizer, and weather [1].…”
Section: Characteristics Of Gmsh Crop As Ensiling Materials and Poten...mentioning
confidence: 99%
“…Sunn hemp (SH, Crotalaria juncea, L.) is an annual legume originating from India [1]. This plant species grows fast, has high seed yield, is tolerant of low fertilizer conditions, and is easily harvested or plowed into soil.…”
Section: Introductionmentioning
confidence: 99%
“…It finds uses in industry as a source of paper-pulp, currency paper, cigarette paper, tissue paper etc. This crop has the potential to be used as a forage crop (Burke et al, 2011;Garzon et al, 2020) on account of higher biomass of its foliage (Cho et al, 2015) and availability of essential nutrients in its feedstock (Cantrell et al 2010). It has the potential of reducing use of synthetic chemicals from agricultural system.…”
Section: Introductionmentioning
confidence: 99%